Peningkatan Pengetahuan pada Pasangan Calon Pengantin tentang Perencanaan Kehamilan melalui program “Secanting” - Wuri Widi Astuti (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2023)
Preconception is care before pregnancy with a span of three months to one year before conception. The "Secanting" program, which stands for “Sosialisasi dan Edukasi Calon Pengantin itu Penting” as a program for the bride and groom to receive education about physical and psychological health before facing marriage so that later they can prepare for the pregnancy process well to prevent malnutrition, prepare the body for changes during pregnancy. , prevent obesity, prevent the risk of miscarriage etc. The purpose of this activity is that participants are expected to know about Healthy Pregnancy Planning. The method used in this activity was to provide counseling to the prospective bride and groom as many as 10 participants, which was carried out at the Puncu Health Center, Puncu District, Kediri Regency on September 5-8, 2022. This activity was carried out in 3 stages, namely pre-testing, providing counseling and followed by a post test. The results of these activities indicate that there is an increase in the knowledge of the participants and the enthusiasm of the participants in participating in the extension activities. Providing information, especially health problems in the community, is very important, with the intensive information that is heard or obtained by individuals, it can increase the knowledge of the prospective bride and groom, especially about pregnancy planning.